Introduction to set theory - Hrbacek, Karel, 1944- (Monographs and textbooks in pure and applied mathematics, 1999)
"Thoroughly revised, updated, expanded, and reorganized to serve as a primary text for mathematics courses, Introduction to Set Theory, Third Edition covers "the basics" - relations, functions, and orderings; finite, countable, and uncountable sets; and cardinal and ordinal numbers - in nine chapters perfect for a one-quarter or one-semester course ... provides five additional self-contained chapters to supplement the basic course or serve as a second-semester syllabus ... consolidates the material on real numbers into a single updated chapter affording flexibility in course design ... supplies end-of-section problems, with hints, of varying degrees of difficulty ... Karel Hrbacek is Professor in the Department of Mathematics, City College, City University of New York. *** Thomas Jech is Professor of Mathematics at Pennsylvania State University, University Park.